1282 An Analysis of Retinopathy of Prematurity Requiring Treatment Over 5Years Period in Our Neonatal Unit. (October 2012) - Kahlil, A; Murphy, AM; O'Leary, O; Stack, T; Sreenan, C; Philip, R
Abstract : Background: Proliferative retinopathy occurs primarily in premature LBW infants as a result of incomplete vasculogensis of the retina at the time of birth. It can be mild, self limiting with no visual defects or progressive leading to blindness. Screening guidelines: Birth weight < 1.5Kg. Gestational ane < 32 weeks. Birth weight 1.5kgs– 1.8kgs and/or Gestational age 32–34 weeks (if received supplementary oxygen for ≥ 12hours. If one twin is in the screening criteria and has eye changes. Aim: To review the number of babies < 1500g, and or Gestational age of < 32/40 who developed ROP required treatment, focusing on infants < 1Kg. Methods: Retrospective chart review of babies born in the Regional Maternity Hospital Limerick between 1 st Jan 2007 and 31st Dec 2011 with ROP requiring treatment. Results: During the study period a total of 225 infants with B.wt < 1500g and/or G.A < 32/40 were admitted to the neonatal unit. All these infants were screened for ROP as per unit guidelines. 93.3% (N=210) infants were < 32/40, and 83%(N=187)< 1500g, of these 28%(N=64) infants weighed less than 1Kg. There were 10 infants (4.4%) who developed ROP requiring treatment, 9 of these infants were in the ELBW category, the tenth baby was only 40gs over the criteria for VLBW(B.wt 1040gs). All 10 babies have disease in zone 2.7 stage2. 2stage1 and one had stage 4. Conclusion: In our unit 10 infants(4.4%)received treatment for ROP over the 5 years period 2007–2011. Our figures are comparable to those reported by Vermont Oxford Network database 2010.